Lymphoma under disguise of conjunctivitis (clinical observations) - I. E. Panova; Ju. N. Vinogradova; E. V. Samkovich (Российский офтальмологический журнал, 2019)
We present two clinical cases of conjunctival lymphoma, the disease which is classified as a malignant tumor of the eye. Conjunctival lymphoma has systemic involvement. Patients presented in our monitoring study received a conservative treatment for chronic conjunctivitis over a long period of time. The article considers the diagnostics and treatment plan of lymphoproliferative eye disease, which allows an increased effectiveness of treating.